Drug Advertising in Brazil: what has changed? (Research, Society and Development, 2021)
The pharmaceutical industry takes advantage of the drug propaganda as the main strategy to influence prescribers and promote sales. In order to guide this market, the Brazilian Sanitary Regulation has begun in 1976 by the creation of the Sanitary Surveillance Law nº 6360. The ethical parameters for the drug propaganda in Brazil are guided by standards defined by the World Health Organization (WHO) in 1988, which are the basis for the elaboration of the current Directors' Collegiate Resolution (RDC) 96/2008. For the purpose of comprehension of the actual scenario, this study verified the legitimacy of the content of the drug propagandas directed to the public, which uses the requirements of Nacional Agency of Sanitary Surveillance (ANVISA) as guidelines. Among the illegalities, 65% of the propagandas didn’t show the recommended slogan “if the symptoms persist, your doctor may be consulted”. The results obtained reaffirm the need of constant supervision of the propagandas in order to reduce the damage to the population health.